(untitled) (Impact: Journal of Transformation, 2026)
Globally, more than 400,000 plant species are used for medicinal purposes. For centuries, African communities have relied on indigenous herbal medicine for the prevention and treatment of a wide range of diseases. Despite the introduction and widespread adoption of Western medicine, many African societies continue to depend on herbal remedies, particularly for ailments perceived to respond poorly to conventional biomedical treatment. Herbal medicine is also commonly regarded as more affordable and as having fewer side effects than Western pharmaceuticals, whose high cost often exceeds the purchasing power of many populations. This paper examines indigenous herbal medicine among the Agikuyu community, with particular emphasis on practices that predate colonialism and remain relevant in contemporary society. The study focuses on major medicinal trees whose names have been used to designate geographical spaces where they naturally grew or once existed. In several cases, environmental degradation has led to the disappearance of these trees, leaving behind place names whose original ecological and medicinal significance is no longer widely recognized by present-day inhabitants. The paper discusses the nutritional and medicinal value of these trees, the ailments they are used to treat, and the belief systems that underpin their use. The study further explores the continued relevance of herbal medicine in addressing both persistent and emerging diseases, including HIV/AIDS, cancer, and COVID-19, while highlighting the challenges facing indigenous herbal practices in the modern context. Data were collected through oral interviews with scholars, herbalists, and individuals aged 50 years and above who have used herbal remedies, and were supplemented by relevant secondary literature. The study underscores the need for accurate knowledge regarding the efficacy and appropriate use of indigenous herbs, alongside increased awareness of potential side effects, contrary to the widespread assumption that herbal medicine is entirely safe. It also emphasizes the importance of preserving indigenous medicinal knowledge for future generations, particularly through place names as cultural and ecological markers, which can contribute to community resilience and adaptation in the face of climate change.